From conflict to catastrophe: Russia-Ukraine tensions ripple across - Saranya ANTONY,Ph.D (Bulletin of "Carol I" National Defense University, 2023)
This paper is an analysis of the Ukraine crisis in 2014 evolving to 2022 as the prelude to the Russia-Ukraine fullfledged war that started in February 2022. The escalating conflict between Russia and Ukraine has reverberated beyond their borders, with the active involvement of key international actors such as the European Union (EU), the North Atlantic Treaty Organization (NATO), and the United States (US) in the conflict zone. Notably, the President of Russia, Vladimir Putin, visited the Kherson and Luhansk regions, further exacerbating tensions in the area. Preceding these events, Russia organized a referendum on 20 September in Donetsk, Luhansk, Zaporizhzhia, and Kherson, wherein enthusiasm for joining the Russian Federation was expressed. These developments are perceived as manifestations of Russia’s dissatisfaction with Ukraine’s political decisions. The conflict’s initiation in 2022 can be attributed to Ukraine’s aspirations to align itself with NATO and the EU, which sparked Russia’s aggressive actions. Despite Ukraine’s efforts to regain control of Crimea and restore its sovereignty, exemplified by the formation of the Crimea Platform at its first Summit in 2021 with the backing of the EU and NATO, the situation has escalated into a full-scale war. By examining the sequence of events and the underlying geopolitical dynamics, this paper aims to shed light on the complexities of the Russia-Ukraine conflict and its shift into a catastrophic war. The findings contribute to a deeper understanding of the interplay between political decisions, regional ambitions, and the global ramifications of military aggression in contemporary international conflicts.